STUDI PENYEBARAN SPASIAL PALEM DI HUTAN LINDUNG GUNUNG SLAMET, JAWA TENGAH [Study on Palm spatial distribution at Gunung Slamet Nature Forest, Central Java] - Insani Widya Astuti; Siswoyo Siswoyo; Himmah Rustiami (Scripta Biologica, 2018)
Ecological studies and the spatial distribution of two forest ecosystem, natural forest and mixed forest, on Mount Slamet, Baturaden, Central Java has been done. There are 12 species of palms in natural forests, Calamus asperimus, C. heteroideus, C. javensis, Calamus sp. 1, Calamus sp. 2, Caryota maxima, C. mitis, Daemonorops rubra, Pinanga coronata, P. javana, Plectocomia elongata, and Salacca zalacca. While in the mixed forest were found six species of palm that were C. asperimus, C. ciliaris, Caryota maxima, Pinanga coronata, P. javana, and Plectocomia elongata. The species that had highest Importance Value Index (IVI) in the two types of ecosystems were Pinanga coronata. Pattern of its distribution both in natural and mixed forests have Morisita index value> 0. This value means that palm has a clustered distribution pattern. The highest spatial distribution of natural palm forest was found in 8-15% slopee class and height class 1,100 - 1200 m asl. Whereas for mixed forest it is found mostly in slopee class 8-15% and height class 900 - 1,000 m asl.